Website-Based Adolescent Mental Health Disorders Screening Application Design - Rahman, Irpan Ali; Nurapandi, Adi; Sundewi, Alis; Setiawan, Henri; Rahayu, Rita (GLOBAL HEALTH SCIENCE GROUP, 2024)
Mental health is a fundamental human right for individual, community, and socio-economic development. There are external and internal factors that can cause a person to experience mental problems. There are various factors contributing to the decline in the mental health of children and adolescents, such as economic problems, education, and the health crisis. The system used to help improve mental health is currently conventional, namely face-to-face between medical personnel and patients. This research aims to develop a